Growth Mindset dan Innovative Behavior Guru: Peran Mediasi Resilience dan Wellbeing - Putranta, Martinus Parnawa; Sigit, Anto (Modus, 2026)
The purpose of this study is to examine the relationship between growth mindset and innovative behavior among teachers, with resilience and wellbeing as possible moderators. Drawing on mindset theory and psychological resource perspectives, this study employs a quantitative approach using a cross-sectional survey design. Data were collected from 227 teachers working in faith-based elementary, junior high, senior high, and vocational schools in Central Java and Yogyakarta, Indonesia. Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 was used for data analysis. The results reveal that growth mindset does not have a direct effect on innovative behavior. However, growth mindset significantly influences resilience and wellbeing, both of which, in turn, positively affect innovative behavior. Further analysis confirms that resilience and wellbeing fully mediate the relationship between growth mindset and innovative behavior. These findings suggest that cognitive orientation alone is insufficient to stimulate innovation unless supported by psychological stability and adaptive capacity. This study contributes to the literature by highlighting the central role of resilience and wellbeing in translating growth mindset into innovative work behavior in educational settings. Practically, the findings emphasize the importance of developing supportive organizational environments that strengthen teachers’ psychological resources to foster sustainable innovation in schools. Keywords: growth mindset; resilience; wellbeing; innovative behavior; teachers.   Penelitian ini bertujuan untuk mengkaji pengaruh growth mindset terhadap innovative behavior guru dengan resilience dan wellbeing sebagai variabel mediasi. Berlandaskan teori mindset dan perspektif sumber daya psikologis, penelitian ini menggunakan pendekatan kuantitatif dengan desain survei cross-sectional. Data dikumpulkan dari 227 guru yang mengajar di sekolah dasar, menengah pertama, menengah atas, dan kejuruan berbasis nilai di wilayah Jawa Tengah dan Daerah Istimewa Yogyakarta. Analisis data dilakukan menggunakan Partial Least Squares–Structural Equation Modeling (PLS-SEM) dengan bantuan perangkat lunak SmartPLS 3. Hasil penelitian menunjukkan bahwa growth mindset tidak berpengaruh langsung terhadap innovative behavior. Namun demikian, growth mindset berpengaruh positif terhadap resilience dan wellbeing, yang selanjutnya secara signifikan meningkatkan innovative behavior. Pengujian mediasi mengonfirmasi bahwa resilience dan wellbeing memediasi hubungan antara growth mindset dan innovative behavior. Temuan ini mengindikasikan bahwa orientasi kognitif saja belum cukup untuk mendorong inovasi tanpa didukung oleh kondisi psikologis yang adaptif dan sejahtera. Penelitian ini memberikan kontribusi teoretis dengan menegaskan peran penting resilience dan wellbeing dalam menjembatani growth mindset dan perilaku kerja inovatif. Secara praktis, hasil penelitian menekankan perlunya kebijakan organisasi pendidikan yang mendukung kesejahteraan dan ketahanan psikologis guru guna mendorong inovasi yang berkelanjutan. Kata kunci: growth mindset; resilience; wellbeing; innovative behavior; guru